KEDUDUKAN PEREMPUAN DALAM IBADAH (Studi Kitab 1 Timotius 2:11-12) - Nurelni Limbong (Jurnal Teologi Cultivation, 2018)
Abstrac The aim of this research is to dscribe concept of the position of women in the worship according to 1 Thimothy 2:11-12 and to formulated what can be reflected in this time? Is the interpretation of this chapter still relevant in the midst of contemporary life? This research is used by descriptive qualitative research methods with using literature (library research). The interpretation that is use in this research is exegesis method with the right step to get the right interpretation. With the literature that have a relation with the title, the writer try to review 1 Thimothy 2:11-12 to get the clear meaning, point out view that was said by the writer of this hook about the position of women in the worship. In this chapter Paul said a women can't teach and she is better keep silence. Paul said these case have a corelation with the patriarch culture at the time. Paul aim to prevent women from teacher heretical at the time. This teaching is actually addressed to the woman who was involved in the heresy/ false, who have abuse the ercercise of power that is true in the church. So Paul said that such matter is not to be understood universally. From this research or exegesis the writer conclude that the woman also be used in God's work, a woman also can be a servant of God because nor only man can serve God woman also called to do the same thing. Proper or not is not about gender. Because man or women are same in the presence of God So. it's not true when this chapter be a reason to limiting the space of woman in the service both in the church and in the family and society. Key words: the position of women, worship